Role of additional posterior barrage laser in type 1 zone 2 retinopathy of prematurity: A randomized trial - Harika Regani; Parijat Chandra; Devesh Kumawat; Rohan Chawla; Ramesh Agarwal; Rajpal Vohra (Indian Journal of Ophthalmology, 2023)
Purpose: The efficacy of additional barrage laser posterior to ridge in advanced stage 3 or stage 4 retinopathy of prematurity (ROP) is established, but its role in early stages is not defined. The objective was to study the efficacy of additional posterior barrage laser in type I zone 2 disease. Methods: In a randomized trial, patients with type I zone 2 ROP were recruited between February 2016 and May 2017. One eye of each baby was randomized into study and control groups, respectively. Laser photocoagulation anterior to ridge was given in the control group, and additional posterior barrage laser was performed in the study group. The outcome measures were time to complete ridge regression and final cycloplegic refraction at 3 months post-laser. Results: Forty patients (40 eyes per group) completed the required follow-up. The mean birth weight and gestational age were 1357 ± 338 g and 29.72 ± 2.57 weeks, respectively. The mean post-conceptional age during laser was 36.67 ± 3.23 weeks. The number of eyes achieving ridge regression in control and study groups was 8/40 (20%) and 27/40 (67%) at 2 weeks (P = 0.001) and 39/40 (97%) and 40/40 (100%) at 4 weeks (P = 0.4). The mean time to complete ridge regression was 3.74 ± 1.17 weeks and 2.62 ± 0.91 weeks in control and study groups, respectively (P < 0.001). The mean spherical equivalent at 12 weeks in control and study groups was -1.9 ± 2.3 Diopters and -2.4 ± 2.6 Diopters, respectively (P = 0.41). Conclusions: Additional posterior barrage laser leads to significantly faster regression of type 1 zone 2 ROP without increasing induced myopia and thereby might be a useful adjunct to conventional treatment in selected cases. Trial registration number: CTRI/2018/05/013779